I-V Curves of an Apigenin Dye and Their Analysis by a New Parabolic Function - Sanusi, Kayode; Ajayi, Olukayode S.; Borisade, Adegoke O.; Elusiyan, Regina B.; Yilmaz, Yusuf; Ceylan, Ümit (Frontiers in Chemistry, 2021)
A new parabolic function for I-V curves’ analysis has been proposed. The new “analytical tool” provides a simple way to describe photophysical processes at an approximately monolayer surface of a dye-sensitized solar cell. It may now be possible to estimate factors such as hole–electron recombination, surface defects, and electron diffusion at the semiconductor layer. The theoretical approach that was previously reported by our group for predicting the photovoltaic performance of potential dye sensitizers has also been validated. The experimental photovoltaic and DFT/TD-DFT data of apigenin and those of the highly rated black dyes were used for the validation.